Beyond p-values: a cross-sectional umbrella review of chemotherapy-induced peripheral neuropathy treatments - Ye, Alice L.; Abdi, Salahadin (Frontiers in Pain Research, 2025)
IntroductionChemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of neurotoxic chemotherapy agents, significantly impacting the daily lives of many cancer survivors. Despite thousands of articles published on CIPN, we remain no closer to a successful treatment regimen for the condition. In recent years, several new clinical trials and systematic reviews have been published, many exploring nonpharmaceutical interventions, prompting the need for a comprehensive synthesis of this emerging evidence.MethodsWe conducted an umbrella review to identify and appraise the 19 systematic reviews (SRs) published in 2023 that examined randomized controlled trials (RCTs) for established CIPN treatment. We focused our analysis on the three most researched treatment options: oral drugs, exercise, and acupuncture. RCTs not previously synthesized together were reviewed, and effect size analyses were performed to allow readers to interpret the existing literature beyond binary p-values.ResultsOur analysis of RCTs revealed the following key findings. For cancer survivors with CIPN after completing chemotherapy, serotonin-norepinephrine reuptake inhibitors (SNRIs) as well as acupuncture provided at least short-term relief for pain and sensory symptoms. For patients with CIPN who were actively undergoing chemotherapy, home-based balance and strength training exercises appeared to alleviate symptoms. Effect size analyses highlighted variability in treatment responses, underscoring the limitations of relying solely on p-values to assess intervention efficacy.DiscussionThrough an umbrella review approach, we demonstrate that SRs are often less systematic than expected. None of the 19 SRs captured all relevant RCTs within their search timeframe. However, by cross-referencing SRs, we identified 41 RCTs across 42 publications, illustrating the feasibility of an umbrella review approach to uncover relevant trials. Furthermore, many SRs exhibited methodological concerns that limit the interpretability of their findings. Finally, we discuss multiple opportunities for refining methods and reporting in future CIPN treatment trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024508283, PROSPERO (42024508283).